2007
DOI: 10.1093/brain/awm131
|View full text |Cite
|
Sign up to set email alerts
|

The motor system shows adaptive changes in complex regional pain syndrome

Abstract: The complex regional pain syndrome (CRPS) is a disabling neuropathic pain condition that may develop following injuries of the extremities. In the present study we sought to characterize motor dysfunction in CRPS patients using kinematic analysis and functional imaging investigations on the cerebral representation of finger movements. Firstly, 10 patients and 12 healthy control subjects were investigated in a kinematic analysis assessing possible changes of movement patterns during target reaching and grasping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
198
0
19

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(229 citation statements)
references
References 84 publications
12
198
0
19
Order By: Relevance
“…Cortical reorganisation in regions associated with the body schema (i.e. primary somatosensory cortex, posterior parietal lobe) have been revealed by brain imaging, providing further evidence of body schema disruption [27,28,29,34].…”
Section: Introduction "If the Pain Is Very Intense Even If I Am Toucmentioning
confidence: 91%
See 2 more Smart Citations
“…Cortical reorganisation in regions associated with the body schema (i.e. primary somatosensory cortex, posterior parietal lobe) have been revealed by brain imaging, providing further evidence of body schema disruption [27,28,29,34].…”
Section: Introduction "If the Pain Is Very Intense Even If I Am Toucmentioning
confidence: 91%
“…Importantly, post-parietal lesions typically result in spatial deficits and clinical disturbances in body representation [39]. Although lesions are not known in CRPS, evidence of abnormal increased neural activation within both parietal lobes has been shown [29]. Furthermore, the degree of motor impairment correlated with activations of the parietal and motor cortices [29].…”
Section: Central Mechanisms: a Feasible Explanationmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetoencephalography (MEG) studies have identified increased activity in the primary motor cortex contralateral to the CRPS affected limb in patients with upper limb CRPS (Maihöfner et al 2007). This has been shown to correlate with poor function in motor planning tasks, particularly those that require integration with visual and proprioceptive cues such as gripping an object.…”
Section: Motor Problemsmentioning
confidence: 99%
“…For example, the CRPS patients can have altered hand representation as a sign of cortical reorganization (Di Pietro, Stanton, Moseley, Lotze, & McAuley, 2015; Juottonen et al., 2002), and some of the observed brain alterations are associated with clinical characteristics of CRPS, such as motor dysfunction (Maihöfner et al., 2007). …”
Section: Introductionmentioning
confidence: 99%